2019
DOI: 10.1089/tmj.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Telemedicine on Teamwork and Workload in Pediatric Resuscitation: A Simulation-Based, Randomized Controlled Study

Abstract: In this simulation-based study, a telepresent team leader was associated with increased team workload compared to usual care. However, no differences were noted in teamwork and processes of care metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Teamwork can be facilitated through technology. Technology, such as telecommunication, facilitates teamwork as it creates the opportunity to involve and interact with professionals from a distance [271][272][273]. Technology also creates opportunities to exchange information through information platforms [276,277].…”
Section: Facilitating Toolsmentioning
confidence: 99%
“…Teamwork can be facilitated through technology. Technology, such as telecommunication, facilitates teamwork as it creates the opportunity to involve and interact with professionals from a distance [271][272][273]. Technology also creates opportunities to exchange information through information platforms [276,277].…”
Section: Facilitating Toolsmentioning
confidence: 99%
“…While many studies described the use of provider-to-provider telemedicine involving a remote specialist, the optimal role for the provider delivering telemedicine and data on clinical efficacy is limited [20][21][22]. Butler et al [23] investigated the impact of telemedicine when involving a senior physician as a remote team leader and showed that workload (measured by NASA-TLX) was significantly increased with a remote leader. Fang et al [5] analyzed data from resuscitations with or without an additional telemedicine specialist as a team leader and demonstrated improvement in the quality of neonatal resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between the two groups in the subjectively perceived overall workload. Neonatal resuscitations are stressful events in most circumstances, and telemedicine is associated with increased workload compared to a physically present team leader [23]. Modalities need to be explored to decrease the workload when using telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Telesimulation occurs with either (1) one learner group remotely watching a simulation being performed by another group of learners and debriefing together, or (2) a remote instructor watching the learners and facilitating a debrief. This approach allows for extension of expensive and limited resources to help educate healthcare providers without access to traditional simulation [ 54 , 55 ]. During the SARS-CoV-2 pandemic, due to constraints on social gatherings, telesimulation was used in some institutions [ 56 , 57 ].…”
Section: Simulation Settingsmentioning
confidence: 99%